Passive Circulation Suppression Strategy of MMC Converter in New TPSS - SONG Pinggang; DONG Hui; ZHOU Zhenbang; WU Jizhen; SUN Nannan (机车电传动)
In order to solve the problems of excessive power and low power quality in traction power supply system (TPSS) of electrified railway, a new TPSS was introduced. Modular multilevel converter (MMC) was used to construct a DC grid between the grid and the contact network, which would generate interphase circulation because of the voltage difference between MMC bridge arms, affecting the system operation. From the viewpoint of energy control, this paper proposed a passive suppression strategy. The EL model of interphase circulation was established in dq coordinate system. The passivity of circulation was proved by passive control theory. The appropriate passivity control law was selected to make the system energy actual value converge quickly to the expected value by using the method of injecting damping. Three phase single-phase traction power supply system model was built on the PSCAD/EMTDC simulation platform. The results showed that energy was controlled by changing the number of sub modules in the input state, the sum of the upper and lower arm voltages approached the DC voltage to achieve the purpose of suppressing circulation.